Individualised and instrumentalised? Critical thinking, students and the optics of possibility within neoliberal higher education. Issue 5 (20th October 2021) - Danvers, Emily
ABSTRACT: This paper explores the state of critical thinking in higher education's everyday pedagogical encounters, against the backdrop of increasing commodification and marketisation. Illustrated by observation, focus group and interview data from 15 first-year undergraduate social-science students at a UK research-intensive university, I explore how neoliberal modes of governmentality create, reproduce and legitimate specific forms of critical think ing and critical think ers . First, I describe how dominant discourses of critical thinking as a commodified technology for assessment rub up against understandings of critical thinking as socio-political protest – using data from students and those teaching them. I then explore the positioning of critical thinking as emotional self-surveillance and unpack the consequences of this politics of reflection over resistance. Using Barad's notion of the 'apparatus' as a contextualising optic of possibility, I argue that while varied forms of criticality exist within the multifarious entanglements constituting the 'neoliberal' academy, instrumentalised and individualised practices come to matter and are valorised. This produces pedagogic and political consequences for thinking critically in and about higher education.